Clinical significance of ultrasonic placental grading during third trimester in hypertensive disorders in pregnancy and its correlation with fetal outcome in tertiary care centre - Naik, Aruna; Khoiwal, Susheela; Sharma, Nisha; Aarthy, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hypertension is one of the common complications in pregnancy and contributes significantly to maternal and perinatal morbidity and mortality. The aim of the present study was to study placental grading by grading by ultrasonography in pregnancy complicated with hypertension and normotensive gravidas. To compare the foetal outcome regarding placental grading and its correlation pattern of placental grade distribution, type of delivery, foetal distress, birth asphyxia, foetal maturity, perinatal morbidity and mortality. Methods: The present study was conducted for a period of 12 months, which included 200 patients who attended OPD at PDRMC, Udaipur. Inclusion criteria was hypertensive pregnant women with BP >140/90 mmHg. Exclusion criteria was Pregnancy associated with other medical disorders, twin gestation, renal and cardiovascular disease and diabetes mellitus. Results: 100 pregnant women with preeclampsia as study group. The most common age group in study group is 22-23 Years. The grade III placenta was found early third trimester in study group. Caesarean delivery was more common mode of delivery in grade III placenta. In foetal outcome small for gestational age was more among the grade III placenta. Foetal distress, birth asphyxia, perinatal mortality, morbidity more among the grade III placenta among the study group. Conclusions: Foetal complications were significantly more in study group compared to control group. Ultrasound placental grade III was statistically significant in correlating with foetal complications like foetal distress, birth asphyxia, perinatal morbidity and mortality.